WORKATION PHENOMENON AND HOTEL SELECTION FOR HOTEL ROOM DESIGN CONSIDERATIONS - Anindita Dara Fitriani; Yuni Maharani (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
This study explores the factors influencing hotel selection for workation. The term workation, derived from the combination of the words